Physical activity coaching in patients with interstitial lung diseases: A randomized controlled trial - Breuls, Sofie; Zlamalova, Tamara; Raisova, Katerina; Blondeel, Astrid; Wuyts, Marieke; Dvoracek, Martin; Zurkova, Monika; Yserbyt, Jonas; Janssens, Wim; Wuyts, Wim; Troosters, Thierry; Demeyer, Heleen (Chronic respiratory disease, 2024)
OBJECTIVES: Physical activity is reduced in patients with interstitial lung disease (ILD) and physical inactivity is related to poor health outcomes. We investigated the effect of a telecoaching intervention to improve physical activity in patients with ILD. METHODS: Eighty patients with ILD were randomized into the intervention or control group. Patients in the intervention group received a 12-week telecoaching program including a step counter, a patient-tailored smartphone application, and coaching calls. Patients in the control group received usual care. Physical activity (primary outcome), physical fitness and quality of life were measured at baseline and 12 weeks later with an accelerometer, 6-min walking test and quadriceps muscle force and the King's Brief Interstitial Lung Disease questionnaire (K-BILD). RESULTS: Participation in telecoaching did not improve physical activity: between-group differences for step count: 386 ± 590 steps/day, p = .52; sedentary time: 4 ± 18 min/day, p = .81; movement intensity: 0.04 ± 0.05 m/s2, p = .45). Between-group differences for the 6-min walking test, quadriceps muscle force and K-BILD were 14 ± 10 m, p = .16; 2 ± 3% predicted, p = .61; 0.8 ± 1.7 points, p = .62 respectively. CONCLUSIONS: Twelve weeks of telecoaching did not improve physical activity, physical fitness or quality of life in patients with ILD. Future physical or behavioural interventions are needed for these patients to improve physical activity.
Keywords: průzkumy a dotazníky; Surveys and Questionnaires; mentoring; Mentoring; Lung Diseases, Interstitial; intersticiální plicní nemoci; Exercise; Humans; lidé; cvičení; kvalita života; Quality of Life